Applications of radiation in photodiagnosis and photodynamic therapy - Entract, Guy (2020)
The application of radiation to porphyrin-based photosensitisers for the purposes of photodiagnosis and photodynamic therapy have been described in an effort to explore combined therapies, which seek to extend the use of photodynamic therapy beyond its traditional applications. A fluorine-18 radiolabelled photosensitiser has been developed to combine photodynamic therapy with positron emission tomography (PET) into a single “theranostic agent”. Synthesis of this novel theranostic agent was carried out through the conjugation of a cationic water-soluble porphyrin bearing an azide moiety to a fluorine-18 radiolabelled PEG chain bearing an alkyne moiety via a copper-catalysed azide-alkyne cycloaddition (CuAAC). A biological evaluation of the theranostic agent was undertaken in vitro, exhibiting good uptake into the HT-29 human cancer cell line. It was the first time a porphyrin labelled with fluorine-18 had been shown to have retained photocytotoxicity following radiolabelling. In vivo evaluation confirmed uptake into neoplastic tissue and demonstrated potential as a radiotracer for (PET). Several suitable nanoparticles were synthesised for the potential to generate visible light under the irradiation of hard X-rays by scintillation pathways. Many of the nanoparticles developed were synthesised for the first-time using microwave-assisted syntheses, which was found to optimise their characteristics and had not previously been tested for their potential as scintillators. An entirely new EuWO4 scheelite morphology was discovered in nanoparticle form, which has not previously been achieved and was found to be a scintillator with good potential. A range of scintillating-nanoparticle photosensitiser conjugates (ScNP-PS) were developed by the functionalisation of scintillating nanoparticles and conjugation to a porphyrin photosensitiser. Preliminary evaluation of conjugates was tested by irradiation using energy of 160 keV, whilst singlet oxygen generation was measured spectrophotometrically using a singlet oxygen probe. All the peptide coupled conjugates displayed 1O2 generation, with the rare earth fluorides La1-xEuxF3 and Lu1-xEuxF3 exhibiting the best results.
HydraID: hull:17799 Hydra Discover Access Group: public ETD Collection: ETDChemistry
Keywords: Chemistry